Nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance as well as preparation method and application of nanofiber diaphragm

By coating lithium nitrate on the nanofiber separator of the intermediate layer of the lithium metal battery and processing it with LiNO3 solution, the problems of lithium dendrites growth and low Coulomb efficiency are solved, high ionic conductivity and strong liquid absorption performance are achieved, and the cycle life of the battery is extended and the cost is reduced.

CN119725992AActive Publication Date: 2025-03-28NINGBO ROUCHUANG NANO TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510106695.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-03-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

The application of the intermediate layer of lithium metal batteries leads to hindered ionic conductivity, resulting in lithium dendrites growth and low Coulomb efficiency, which in turn affects the performance and safety of the battery.

Method used

A nanofiber separator consisting of a skeleton fiber layer, a nanofiber layer and a polymer network layer is used, and lithium nitrate is coated on its surface, and treated with LiNO3 solution to improve the ionic conductivity and liquid absorption performance of the separator.

Benefits of technology

It significantly improves the ionic conductivity and liquid absorption performance of the lithium metal negative electrode, inhibits the growth of lithium dendrites, extends the cycle life of the battery, and reduces the production cost of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725992A_ABST
    Figure CN119725992A_ABST
Patent Text Reader

Abstract

The invention discloses a nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance as well as a preparation method and application thereof, and the preparation method comprises the following steps: (1) dissolving lithium nitrate salt to prepare a lithium nitrate solution; (2) pressing the nanofiber diaphragm into an electrode plate and drying the electrode plate in a vacuum drying oven; (3) soaking the nanofiber diaphragm treated in the step (2) in the LiNO3 solution in the step (1) at the temperature of 100-120 DEG C, fully mixing the nanofiber diaphragm and the LiNO3 solution, and coating and filling the lithium-loving nitrate on the nanofiber diaphragm; and (4) drying the nanofiber diaphragm obtained after treatment in the step (3) under the condition of 40-100 DEG C to obtain the nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance. According to the invention, the LiNOO-treated nanofiber diaphragm intermediate layer is beneficial to maintaining the integrity of a lithium metal and diaphragm interface, reducing side reactions in the battery and prolonging the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium metal batteries, and in particular relates to a nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance, a preparation method and an application thereof. Background Art

[0002] Lithium-ion batteries have become an indispensable core power source for modern portable electronic devices (including mobile phones, laptops, tablets, etc.), electric vehicles, and large-scale energy storage systems due to their excellent characteristics such as high energy density, long cycle life, and low self-discharge rate. With the continuous expansion of these application fields and the iterative upgrading of technology, the expectations for the performance of lithium-ion batteries have become more and more stringent. Taking electric vehicles as an example, their demand for lithium-ion batteries is not only for higher power density to achieve fast charging and strong power output, but also to ensure long driving range. This means that the internal components of the battery, especially the diaphragm, must effectively ensure the stable operation and safety of the battery in the process of efficient transmission of lithium ions.

[0003] The negative electrode is a key component of lithium-ion batteries (LIBs). Currently, most commercial LIBs on the market use graphite as the negative electrode material, and its main function is to accept and collect lithium ions from the positive electrode. However, the development of traditional lithium-ion batteries based on graphite negative electrodes has approached its theoretical capacity limit (372 mAh / g). In comparison, lithium metal batteries have begun to attract the attention of scientific researchers around the world because of their theoretical capacity of up to 3860 mAh / g and low reduction potential of -3.04V (compared to the standard hydrogen electrode). However, the high activity of lithium metal causes lithium metal batteries (LMBs) to face serious safety hazards caused by dendrite growth and low coulombic efficiency during the cycle process. At present, several mainstream solutions have emerged, such as designing functional electrolytes, constructing special three-dimensional current collectors, and modifying artificial solid electrolyte membranes. Their core purpose is to overcome the problem of lithium dendrite growth. The design and modification of lithium-philic interlayers are also widely used in the field of LMBs. For LMBs, the use of lithium-philic interlayers is a key measure to inhibit dendrite growth and give full play to the high capacity advantages of lithium metal batteries. This not only requires the interlayer to have excellent ion conductivity and high electrolyte wettability to achieve liquid retention and rapid ion conduction, but also requires strong chemical stability to avoid side reactions with electrolytes. In addition, the unique lithium-philic mechanism of the interlayer is the core element to achieve dendrite-free lithium metal negative electrodes. The lithium-philic interlayer is closely related to the production cost and battery efficiency of lithium metal batteries. It is no exaggeration to say that the presence or absence of the interlayer directly affects the performance and service life of LMBs.

[0004] LIBs are high energy density batteries. LiCoO2 (LCO) is the first generation of commercial lithium-ion battery cathode materials and still occupies the main market of lithium-ion secondary battery cathode materials. Co in LCO is a scarce strategic metal, which leads to the high cost of LCO. 1-2x Co x Mn x ]O2 (NCM) positive electrode materials are mainly composed of Ni, Co, Mn, etc., among which the content of Co is relatively low. With the development of technology, high-nickel and low-cobalt ternary materials continue to emerge, further reducing costs and making them more economically advantageous in large-scale applications. The cycle performance of NCM materials is better than that of LCO. After multiple charge and discharge cycles, its capacity decay is relatively slow, and it can maintain a high specific capacity, thereby extending the service life of the battery and reducing the frequency and cost of battery replacement. It is especially suitable for application scenarios with high cycle life requirements, such as electric vehicles. Its working principle is as follows: During charging, the positive electrode undergoes an oxidation reaction, e - Through the external circuit from the positive to the negative electrode, the Li inside the battery + The electrolyte goes from the positive electrode to the negative electrode, where a reduction reaction occurs. Contrary to the charging process, a reduction reaction occurs at the positive electrode during discharge. - From the negative electrode to the positive electrode through the external circuit, the Li inside the battery + The electrolyte passes from the negative electrode to the positive electrode, and an oxidation reaction occurs at the negative electrode.

[0005] The energy density and lithium storage capacity of the negative electrode in LIBs are the main factors affecting battery performance, and the corresponding component is the lithium metal negative electrode (LMA). Conventional LMA is mainly composed of pure lithium foil. LMA faces safety hazards and low coulombic efficiency (CE) caused by lithium dendrite growth during the cycle. When the nanofiber separator is used as an intermediate layer, the transfer efficiency of ions and electrons is affected to a certain extent due to the addition of the intermediate layer when the nanofiber separator is combined with LMA. Summary of the invention

[0006] The present invention provides a nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance and a preparation method to solve the problem of lithium dendrite growth and low coulomb efficiency caused by the obstruction of ionic conductivity caused by the current use of the intermediate layer of lithium metal batteries, thereby solving the difficult problem of high energy density lithium metal batteries towards practical application.

[0007] In order to achieve the above-mentioned object, the present invention provides an application of a nanofiber membrane and a lithium nitrate solution in the preparation of a nanofiber membrane with high ionic conductivity and strong liquid absorption performance. The nanofiber membrane is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top, the skeleton fiber layer is interwoven with micron fibers and chemical short fibers, the nanofiber layer is interwoven with nanofibers containing hydroxyl functional groups, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymers partially extend into the nanofiber layer. In the nanofiber membrane, the skeleton fibers account for 11-15wt%, the nanofibers account for 80-84wt%, and the polymer network accounts for 5wt%; The lithium nitrate solution is a 0.5 mol / L-2 mol / L lithium nitrate aqueous solution; The nanofiber membrane is pressed into an electrode sheet and dried in a vacuum drying oven, then immersed in the lithium nitrate solution, fully mixed, and then dried at 40-100° C. to obtain the nanofiber membrane with high ionic conductivity and strong liquid absorption performance.

[0008] The nanofiber membrane has a skeleton fiber ratio of 15wt%, a nanofiber ratio of 80wt%, and a polymer network ratio of 5wt%. The nanofiber membrane has a thickness of 12 um-18 um, a porosity of 80-86%, and an ionic conductivity of 0.70-0.80 mScm -1 , the concentration of lithium nitrate aqueous solution is 1 mol / L.

[0009] The diameter of the nanofiber is 5-100nm; the diameter of the micron fiber is 0.5-1μm, and the length is 10-1000μm; the diameter of the chemical staple fiber is 1-6μm, and the length is 1-12 mm; the nanofiber is at least one of nanocellulose fiber and fibrillated Tencel fiber; the micron fiber is at least one of fibrillated chemical staple fiber, pulp, and micron cellulose fiber; the chemical staple fiber is at least one of PET fiber, PAN fiber, PBO fiber, PA fiber, PI fiber, and aramid staple fiber; the polymer is at least one of aramid, polyacrylonitrile, polyvinylidene fluoride, and polymethyl methacrylate.

[0010] Another object of the present invention is to provide a method for preparing a nanofiber membrane with high ionic conductivity and strong liquid absorption performance, the steps comprising: Step 1. dissolving lithium nitrate salt to prepare a lithium nitrate aqueous solution; Step 2. Pressing the nanofiber separator membrane into an electrode sheet and drying it in a vacuum drying oven; Step 3. At a temperature of 100-120° C., immerse the nanofiber membrane treated in step 2 in the LiNO3 solution in step 1, and mix the two thoroughly, so that the lithium-philic nitrate is coated and filled on the nano-membrane; Step 4. Dry the nanofiber membrane obtained after the treatment in step 3 at 40-100° C. to obtain the nanofiber membrane with high ionic conductivity and strong liquid absorption performance.

[0011] The concentration of the lithium nitrate salt solution in step 1 is 0.5 mol / L-2 mol / L.

[0012] The concentration of the lithium nitrate salt solution in step 1 is 1 mol / L.

[0013] In step 2, the nanofiber membrane is immersed in the LiNO3 solution for 20 min to 60 min.

[0014] In step 2, the thickness of the nanofiber membrane is 12 um-18 um.

[0015] The nanofiber membrane is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top, the skeleton fiber layer is interwoven with micron fibers and chemical staple fibers, the nanofiber layer is interwoven with nanofibers containing hydroxyl functional groups, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymers partially extend into the nanofiber layer. In the nanofiber membrane, skeleton fibers account for 11-15wt%, nanofibers account for 80-84wt%, and the polymer network accounts for 5wt%.

[0016] The nanofiber membrane has a skeleton fiber ratio of 15wt%, a nanofiber ratio of 80wt%, and a polymer network ratio of 5wt%. The nanofiber membrane has a thickness of 12 um-18 um, a porosity of 80-86%, and an ionic conductivity of 0.70-0.80 mScm -1 .

[0017] A nanofiber membrane with high ionic conductivity and strong liquid absorption performance is prepared by the above method. The nanofiber membrane with high ionic conductivity and strong liquid absorption performance comprises a nanofiber membrane and lithium nitrate salt coated on the membrane, and the weight of the lithium nitrate salt is 1.2-1.4% of the weight of the nanofiber membrane.

[0018] A lithium ion battery comprises a shell, a positive electrode sheet, a negative electrode sheet, an electrolyte and an intermediate layer, wherein the intermediate layer is a nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance prepared by the above method, and the thickness of the nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance is 15 um. Beneficial effects: The present invention provides a method for preparing a nanofiber diaphragm with high ionic conductivity and strong liquid absorption performance. The prepared nanofiber diaphragm as a battery intermediate layer has the following advantages: (1) The lithium affinity of the coating layer and the high porosity of the nanofiber diaphragm can improve the ionic conductivity and liquid absorption performance of the lithium metal negative electrode. At the same time, the present invention explores the nanofiber diaphragm treated with the optimal concentration of LiNO3 to maximize the ionic conductivity and liquid absorption performance; (2) The LiNO3 solution is simple and easy to prepare, and can realize the mass production of materials with high ionic conductivity and strong liquid absorption performance, greatly reducing the cost of the market application of lithium metal batteries; (3) A stable interface layer can be formed on the contact interface between the electrode and the intermediate layer, and this interface layer can inhibit the growth of lithium dendrites and extend the battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The liquid absorption strength test of the nanofiber membrane of the present invention, wherein (a) is the liquid absorption capacity test of Example 1, (b) is the liquid absorption capacity test of Example 2, (c) is the liquid absorption capacity test of Example 3, (d) is the liquid absorption capacity test of Example 4, and (e) is the liquid absorption capacity test of Comparative Example 2; Figure 2 The nanofiber separator prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 of the present invention is used as the intermediate layer of the lithium metal negative electrode and Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2 assembled full cell electrochemical impedance spectroscopy (EIS) test; Figure 3 The nanofiber separator prepared in Example 1, Example 2, Example 3, and Comparative Example 2 of the present invention is used as the intermediate layer of the lithium metal negative electrode and Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2 assembled full battery cycle 15 times discharge state intermediate layer XPS characterization test results; Figure 4 The nanofiber separator prepared in Example 2, Comparative Example 1 and Comparative Example 2 of the present invention is used as the intermediate layer of the lithium metal negative electrode and Li[Ni 0.8 Co 0.1 Mn 0.1 ]Electrochemical cycle test of the full battery assembled with O2. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is described below through specific embodiments.

[0021] Comparative Example 1 The method for preparing the nanofiber membrane comprises the following steps: (1) The nanofiber membrane is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top; the skeleton fiber layer is interwoven with micron fibers and chemical short fibers, the nanofiber layer is interwoven with nanofibers containing hydroxyl functional groups, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymer partially extends into the nanofiber layer.

[0022] The micron fiber is at least one of filamentized chemical short fibers, pulp, and micron cellulose fibers; the diameter of the micron fiber is 0.5-1 μm, and the length is 10-1000 μm.

[0023] The chemical short fiber is at least one of PET fiber, PAN fiber, PBO fiber, PA fiber, PI fiber and aramid short fiber. The diameter of the chemical short fiber is 1-6 μm and the length is 1-12 mm.

[0024] The nanofiber is at least one of nanocellulose fiber and fibrillated Tencel fiber.

[0025] The polymer is at least one of aramid, polyacrylonitrile, polyvinylidene fluoride and polymethyl methacrylate.

[0026] (2) In step (1), the skeleton fiber accounts for 15wt%, the nanofiber accounts for 80wt%, and the polymer network accounts for 5wt%.

[0027] (3) Furthermore, the nanofiber membrane has a thickness of 12 um-18 um, a porosity of 80-86%, and an ionic conductivity of 0.70-0.80 mS cm -1 .

[0028] (4) Before use, the wet membrane was filtered, squeezed and cut into small discs with a diameter of 16 mm. The discs were placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air to obtain a nanofiber membrane with a thickness of 15 um.

[0029] Comparative Example 2 A method for preparing a nanofiber separator carrying AgNO3 for an intermediate layer of a lithium metal battery, the steps comprising: (1) Weigh 2 g of AgNO3 particles using an analytical balance and prepare a 1 mol / L AgNO3 solution with deionized water.

[0030] (2) A nanofiber separator with a thickness of 15 μm (prepared by the method of Comparative Example 1) purchased from Ningbo Rouchuang Nanotechnology Co., Ltd. was pressed and cut into small discs with a diameter of 16 mm, and placed in a vacuum drying oven at 60 °C for 12 h to completely remove moisture in the air; (3) Soaking the 15 μm-thick nanofiber membrane in step (2) in the AgNO3 solution in step (1) at 80°C for 30 minutes; (4) The nanofiber membrane prepared in step (3) was placed in an oven at 80 °C to dry out the moisture, and then placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air. The membrane was then stored in a vacuum drying oven. After drying, the weight of the membrane increased by 1.3% relative to the original membrane.

[0031] Example 1 A method for preparing a nanofiber membrane with high ionic conductivity and strong liquid absorption performance, comprising the following steps: (1) Weigh 1 g of LiNO3 particles using an analytical balance and prepare a 0.5 mol / L LiNO3 solution with deionized water.

[0032] (2) The nanofiber diaphragm prepared in Comparative Example 1 was pressed and cut into small discs with a diameter of 16 mm, and placed in a vacuum drying oven at 60 °C for 12 h to completely remove moisture in the air; the surface of the nanofibers is rich in hydroxyl groups, which can adsorb lithium nitrate to form a new pore structure.

[0033] (3) Soaking the 15 μm-thick nanofiber separator in step (2) with the LiNO3 solution in step (1) at 80°C for 30 minutes; (4) The nanofiber membrane prepared in step (3) was placed in an oven at 80°C to dry out the moisture, and then placed in a vacuum drying oven at 60°C for 12 h to completely remove the moisture in the air. The membrane was then stored in a vacuum drying oven. After drying, the weight of the membrane increased by 1% relative to the original membrane.

[0034] Example 2 A method for preparing a nanofiber membrane with high ionic conductivity and strong liquid absorption performance, comprising the following steps: (1) Weigh 2 g of LiNO3 particles using an analytical balance and prepare a 1 mol / L LiNO3 solution with deionized water.

[0035] (2) The nanofiber separator prepared in Comparative Example 1 was pressed and cut into small discs with a diameter of 16 mm, and placed in a vacuum drying oven at 60 °C for 12 h to completely remove moisture in the air; (3) Soaking the 15 μm-thick nanofiber separator in step (2) with the LiNO3 solution in step (1) at 80°C for 30 minutes; (4) The nanofiber membrane prepared in step (3) was placed in an oven at 80 °C to dry out the moisture, and then placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air. The membrane was then stored in a vacuum drying oven. After drying, the weight of the membrane increased by 1.2% relative to the original membrane.

[0036] Example 3 A method for preparing a nanofiber membrane with high ionic conductivity and strong liquid absorption performance, comprising the following steps: (1) Weigh 4 LiNO3 particles using an analytical balance and prepare a 2 mol / L LiNO3 solution with deionized water.

[0037] (2) The nanofiber separator prepared in Comparative Example 1 was pressed and cut into small discs with a diameter of 16 mm, and placed in a vacuum drying oven at 60 °C for 12 h to completely remove moisture in the air; (3) Soaking the 15 μm-thick nanofiber separator in step (2) with the LiNO3 solution in step (1) at 80°C for 30 minutes; (4) The nanofiber membrane prepared in step (3) was placed in an oven at 80 °C to dry out the moisture, and then placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air. The membrane was then stored in a vacuum drying oven. After drying, the weight of the membrane increased by 1.4% relative to the original membrane.

[0038] Example 4 (1) A method for preparing a nanofiber membrane, the steps are the same as those of comparative example 1, except that the proportion of nanocellulose in the nanofiber membrane is different.

[0039] (2) The skeleton fibers account for 25wt%, the nanofibers account for 70wt%, and the polymer network accounts for 5wt%.

[0040] (3) Furthermore, the nanofiber membrane has a thickness of 14 um-20 um, a porosity of 68-74%, and an ionic conductivity of 0.51-0.59 mS cm -1 .

[0041] (4) Before use, the wet membrane was filtered, squeezed and cut into small discs with a diameter of 16 mm. The discs were placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air to obtain a nanofiber membrane with a thickness of 15 um.

[0042] Example 5 (1) A method for preparing a nanofiber membrane, the steps are the same as those of comparative example 1, except that the proportion of nanocellulose in the nanofiber membrane is different.

[0043] (2) The skeleton fibers account for 20wt%, the nanofibers account for 75wt%, and the polymer network accounts for 5wt%.

[0044] (3) Furthermore, the nanofiber membrane has a thickness of 14 um-20 um, a porosity of 69-75%, and an ionic conductivity of 0.58-0.63 mS cm -1 .

[0045] (4) Before use, the wet membrane was filtered, squeezed and cut into small discs with a diameter of 16 mm. The discs were placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air to obtain a nanofiber membrane with a thickness of 15 um.

[0046] Example 6 (1) A method for preparing a nanofiber membrane, the steps are the same as those of comparative example 1, except that the proportion of nanocellulose in the nanofiber membrane is different.

[0047] (2) The skeleton fibers account for 10wt%, the nanofibers account for 85wt%, and the polymer network accounts for 5wt%.

[0048] (3) Furthermore, the nanofiber membrane has a thickness of 11um-18um, a porosity of 81-88%, and an ionic conductivity of 0.61-0.68 mS cm -1 .

[0049] (4) Before use, the wet membrane was filtered, squeezed and cut into small discs with a diameter of 16 mm. The discs were placed in a vacuum drying oven at 60 °C for 12 h to completely remove the moisture in the air to obtain a nanofiber membrane with a thickness of 15 um.

[0050] The performance of the diaphragms prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 was tested, and the test results are shown in Table 1.

[0051] Table 1 Ionic conductivity and liquid absorption height of ultrathin nanofiber separator under the action of LiNO3

[0052] It can be seen from Table 1 that when the ultra-thin nanofiber diaphragm treated with different concentrations of LiNO3 is made into an intermediate layer, the more LiNO3 content is not necessarily better. The best effect is when the nanofiber diaphragm is optimally loaded with LiNO3, so that the nanofiber diaphragm can achieve the optimal ionic conductivity and liquid absorption height. When the nanofiber diaphragm is loaded with moderate LiNO3, the ionic conductivity, liquid absorption height and diaphragm pore size distribution complement each other and reach the optimal level at the same time.

[0053] The nanofiber membranes of Examples 4 to 6 were treated by soaking in LiNO3 solutions of different concentrations in Examples 1 to 3 to prepare nanofiber membranes with the same thickness but different weights of loaded LiNO3 and high ionic conductivity and strong liquid absorption performance, and the ionic conductivity, membrane porosity and pore size distribution range were tested, and the test results are shown in Table 2. The content of nanofibers affects the adsorption of LiNO3. When ultra-thin nanofiber membranes treated with different concentrations of LiNO3 are made into an intermediate layer, the more LiNO3 content is not necessarily better. The nanofiber membrane has the best effect when the loading of LiNO3 reaches the best. The main reason is that the hydroxyl groups loaded by nanocellulose directly affect the adsorption of LiNO3, and the nanofiber content is the best, so that the nanofiber membrane can achieve the best ionic conductivity. When the nanofiber membrane is loaded with moderate LiNO3, the ionic conductivity, membrane porosity and membrane pore size distribution complement each other and reach the best at the same time.

[0054] Table 2 Ionic conductivity and porosity of ultrathin nanofiber separators under the action of LiNO3

[0055] Table 3 Ionic conductivity and porosity of nanofiber membranes of Comparative Example 1 to Example 3 after 15 cycles under the action of LiNO3

[0056] As shown in Table 3, the porosity and other properties of the nanofiber membrane decreased to varying degrees after cycling, and the ionic conductivity increased. It may be that LiNO3 generated new substances with higher ionic conductivity under the electrochemical action, which changed the pore structure distribution and ionic conductivity of the membrane. The low concentration of LiNO3 solution will affect the generation of new substances with higher ionic conductivity, but when too many new substances with higher ionic conductivity are generated, the porosity and pore size of the membrane will be significantly reduced, thereby slowing down the rate at which lithium ions pass through the membrane and reducing ionic conductivity. The more LiNO3 content is not necessarily better. The nanofiber membrane has the best effect when the LiNO3 loading reaches the best, ensuring that the nanofiber membrane reaches the best ionic conductivity and porosity during the cycle.

[0057] The nanofiber separators prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were attached to lithium metal negative electrodes, Li[Ni0.8 Co 0.1 Mn 0.1 ]O2 positive electrode, electrolyte (DME / DOL (1:1, v / v) 1 M LiTFSI) were assembled into a full battery for electrochemical impedance spectroscopy (EIS) test. The Nyquist curve is shown in Figure 2 As shown, the charge transfer impedance Rct of the battery in Example 2 is lower than that in Example 1, Example 3, Comparative Example 1 and Comparative Example 2, which means that the Li + The decrease in transport resistance can effectively promote the migration of lithium ions in the middle layer and improve ionic conductivity. In the electrochemical impedance spectrum, a lower charge transfer impedance Rct is usually associated with better electrochemical performance, because it means that the resistance of the charge transfer process in the electrochemical reaction is smaller, thereby improving the charge and discharge efficiency and rate performance of the battery.

[0058] After being immersed in the LiNO3 solution in the above steps, the nanofiber separator has good ionic conductivity and liquid absorption performance. LiNO3 is a strong electrolyte that will dissociate a large number of lithium ions (Li + ) and nitrate ions (NO3 - ), XPS was used to detect the nanofiber separators prepared in Example 1 and Comparative Example 2 and the lithium metal negative electrode, Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2 positive electrode, electrolyte (DME / DOL (1:1, v / v) 1 M LiTFSI) assembled full battery after charge and discharge characteristics, such as Figure 3 It is found that compared with Example 1, Example 3, and Comparative Example 2, a solid electrolyte interface layer (SEI) rich in Li3N and Li2O with high ionic conductivity are more significantly formed on the surface of the nanofiber separator facing the lithium negative electrode in Example 2, thereby stabilizing the subsequent lithium deposition / stripping. At the same time, the Li2O peak in Example 3 and Comparative Example 2 shows a trend of migration to the left, which means that a more stable Li2O layer is formed on the surface of the nanofiber separator, which may be unfavorable for the migration of lithium ions, because higher binding energy means that lithium ions are more difficult to be extracted from Li2O, which may affect the cycle performance of the battery, and there will be unfavorable charge transfer, resulting in a decrease in the adsorption energy of lithium, thereby affecting the lithium deposition / stripping in subsequent cycles. Compared with Example 2, it is proved that the performance of the nanofiber separator modified by LiNO3 is better than that of the nanofiber separator modified by AgNO3. The reason for this difference is that the lithium deposition / stripping process on the separator of Comparative Example 2 is uneven, and leads to the accumulation of dead lithium.

[0059] After treating the nanofiber separator with LiNO3 solution of different concentrations, when the nanofiber separator is immersed in LiNO3 solution, on the one hand, the additional lithium ions will increase the ion concentration in the electrolyte near the separator, promote the migration of lithium ions in the middle layer and improve the ionic conductivity; on the other hand, NO3 - The presence of ions will interact with other ions in the electrolyte to promote the dissociation of lithium salts and further improve the ionic conductivity. At the same time, the formation of Li3N-rich SEI and high ionic conductivity Li2O allows the uniform deposition / stripping of lithium metal. It is also worth noting that the nanofiber separator with LiNO3 attached has strong liquid absorption and liquid retention properties, optimizes the microenvironment of ion transmission, and effectively improves the overall ionic conductivity of the separator. The SEI film formed by LiNO3 has certain electrochemical stability and interfacial activity. When it exists in the middle layer of the nanofiber separator, it can form a stable interface layer on the contact interface between the lithium metal negative electrode and the middle layer. This interface layer can inhibit the growth of lithium dendrites. Lithium dendrites are an undesirable phenomenon that may occur in lithium-ion batteries during the cycle process. It will pierce the separator and cause the battery to short-circuit, seriously affecting the safety and life of the battery. By inhibiting the growth of lithium dendrites, the nanofiber separator middle layer treated with LiNO3 helps to maintain the integrity of the interface between lithium metal and the separator, reduce side reactions inside the battery, and extend the cycle life of the battery.

[0060] After the nanofiber membrane is treated with LiNO3 solution, the surface chemical properties of the membrane will change. This is because the LiNO3 solution can introduce some polar groups NO3 on the membrane surface. - , changing the charge distribution on the surface of the diaphragm, changing the diaphragm from a relatively hydrophobic state to a more lyophilic state. The lithium ions in LiNO3 may be adsorbed on the surface of the diaphragm, making the surface of the diaphragm positively charged, and the anions in the electrolyte will be attracted, thereby promoting the contact and adsorption of the electrolyte and the diaphragm, and improving the liquid absorption performance of the diaphragm. From the perspective of physical structure, the LiNO3 solution can adjust the pore structure of the nanofiber diaphragm during the immersion process. It may prevent the collapse or blockage of the pores of the diaphragm during the preparation process, making the pores more unobstructed. At the same time, it can also make the pore size distribution more reasonable, which is conducive to the filling and storage of the electrolyte. The pores of the diaphragm treated with LiNO3 solution can better absorb and accommodate the electrolyte, thereby increasing the liquid absorption performance.

[0061] It should be understood that the above description of the preferred embodiment is relatively detailed and cannot be regarded as limiting the scope of patent protection of the present invention. Under the enlightenment of the present invention, ordinary technicians in this field can also make substitutions or modifications without departing from the scope of protection of the claims of the present invention, which all fall within the scope of protection of the present invention. The scope of protection requested for the present invention shall be based on the attached claims.

Claims

1. Application of nanofiber membrane and lithium nitrate solution in the preparation of nanofiber membrane with high ionic conductivity and strong liquid absorption performance, characterized in that: The nanofiber membrane is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top, wherein the skeleton fiber layer is interwoven with micron fibers and chemical short fibers, the nanofiber layer is interwoven with nanofibers containing hydroxyl functional groups, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymers partially extend into the nanofiber layer. In the nanofiber membrane, the skeleton fibers account for 11-15wt%, the nanofibers account for 80-84wt%, and the polymer network accounts for 5wt%; The lithium nitrate solution is a 0.5 mol / L-2 mol / L lithium nitrate aqueous solution; The nanofiber membrane is pressed into an electrode sheet and dried in a vacuum drying oven, then immersed in the lithium nitrate solution, fully mixed, and then dried at 40-100° C. to obtain the nanofiber membrane with high ionic conductivity and strong liquid absorption performance.

2. The use according to claim 1, characterized in that: The nanofiber membrane has a skeleton fiber ratio of 15wt%, a nanofiber ratio of 80wt%, and a polymer network ratio of 5wt%. The nanofiber membrane has a thickness of 12 um-18 um, a porosity of 80-86%, and an ionic conductivity of 0.70-0.80 mS cm -1 , the concentration of lithium nitrate aqueous solution is 1 mol / L.

3. The use according to claim 1, characterized in that: The diameter of the nanofiber is 5-100nm; the diameter of the micron fiber is 0.5-1μm, and the length is 10-1000μm; the diameter of the chemical staple fiber is 1-6μm, and the length is 1-12mm; the nanofiber is at least one of nanocellulose fiber and fibrillated Tencel fiber; the micron fiber is at least one of fibrillated chemical staple fiber, pulp, and micron cellulose fiber; the chemical staple fiber is at least one of PET fiber, PAN fiber, PBO fiber, PA fiber, PI fiber, and aramid staple fiber, and the polymer is at least one of aramid, polyacrylonitrile, polyvinylidene fluoride, and polymethyl methacrylate.

4. A method for preparing a nanofiber membrane with high ionic conductivity and strong liquid absorption performance, characterized in that the steps include: Step 1. dissolving lithium nitrate salt to prepare a lithium nitrate aqueous solution; Step 2. Press the nanofiber membrane into an electrode sheet and dry it in a vacuum oven; Step 3. At a temperature of 80-120° C., immerse the nanofiber membrane treated in step 2 in the LiNO3 solution in step 1, and mix the two thoroughly, so that the lithium-philic nitrate is coated and filled on the nano-membrane; Step 4. Dry the nanofiber membrane obtained after the treatment in step 3 at 40-100° C. to obtain the nanofiber membrane with high ionic conductivity and strong liquid absorption performance.

5. The preparation method according to claim 4, characterized in that: The concentration of the lithium nitrate salt solution in step 1 is 0.5 mol / L-2 mol / L.

6. The preparation method according to claim 4, characterized in that: The concentration of the lithium nitrate salt solution in step 1 is 1 mol / L.

7. The preparation method according to claim 4, characterized in that: In step 2, the nanofiber membrane is immersed in the LiNO3 solution for 20 min-60 min; the thickness of the nanofiber membrane in step 2 is 12 um-18 um.

8. The preparation method according to claim 4, characterized in that: The nanofiber membrane is formed by stacking a skeleton fiber layer, a nanofiber layer and a polymer network layer from bottom to top, the skeleton fiber layer is interwoven with micron fibers and chemical staple fibers, the nanofiber layer is interwoven with nanofibers containing hydroxyl functional groups, and the polymer network layer is interwoven with polymers; the nanofibers partially extend into the skeleton fiber layer, and the polymers partially extend into the nanofiber layer. In the nanofiber membrane, skeleton fibers account for 11-15wt%, nanofibers account for 80-84wt%, and the polymer network accounts for 5wt%.

9. The preparation method according to claim 4, characterized in that: The nanofiber membrane has a skeleton fiber ratio of 15wt%, a nanofiber ratio of 80wt%, and a polymer network ratio of 5wt%. The nanofiber membrane has a thickness of 12 um-18 um, a porosity of 80-86%, and an ionic conductivity of 0.70-0.80 mS cm -1 .

10. A nanofiber membrane with high ionic conductivity and strong liquid absorption performance is prepared by the method according to any one of claims 4 to 9, characterized in that: The diaphragm comprises a nanofiber diaphragm and lithium nitrate salt coated on the diaphragm, and the weight of the lithium nitrate salt is 1.2-1.4% of the weight of the nanofiber diaphragm.

11. A lithium ion battery, characterized in that: It comprises a shell, a positive electrode sheet, a negative electrode sheet, an electrolyte and an intermediate layer, wherein the intermediate layer is the nanofiber membrane with high ionic conductivity and strong liquid absorption performance as claimed in claim 10, and the thickness of the nanofiber membrane with high ionic conductivity and strong liquid absorption performance is 15um.

Citation Information

Patent Citations

  • Lithium battery diaphragm and preparation method thereof

    CN110993868A

  • Preparation method of gel polymer electrolyte diaphragm for lithium-sulfur battery

    CN117239348A

  • Synergistic high-ionic-conductivity carbon film as well as preparation method and application thereof

    CN118040235A

  • Electrospinning of PVDF-HFP: novel composite polymer electrolytes (CPES) with enhanced ionic conductivities for lithium-sulfur batteries

    US20200136113A1